Syntheses, structures, properties of a series of coordination polymers with flexible bis(imidazole) and dicarboxylate ligands. (5th September 2017) - Shi, Lu-Lu; Zhang, Ya-Qian; Han, Shan-Shan; Yang, Zhi; Zhu, Li-Ming; Li, Bao-Long; Li, Hai-Yan
Graphical abstract: Seven coordination polymers with diverse structures were synthesized and characterized. The photocatalytic activity for the degradation of methyl orange by1 and2 was investigated. The luminescence of3 –7 and thermal stability of1 –7 were also investigated. Abstract: Seven coordination polymers, [Co(bix)(ndc)] n (1 ), [Co2 (bix)(glu)2 ] n (2 ), [Zn(bix)(male)]·H2 O n (3 ), [Zn2 (bix)(pim)2 ] n (4 ), [Zn(bix)(aze)] n (5 ), [Zn(bix)(mbda)]·H2 O n (6 ) and [Zn(bix)(adc)] n (7 ), were synthesized (bix = 1, 4-bis(2-methyl-imidazol-1-methyl)benzene, ndc = 1, 4-naphthalenedicarboxylate, glu = glutarate, male = maleicate, pim = pimelate, aze = azelaicate, mbda = 1, 3-benzenediacetate, adc = 1, 3-adamantanedicarboxylate).1 shows an unusual 4-connected self-catenated 3D network.2 is a 6-connected self-catenated 3D network based on the [Co2 (COO)4 ] unit.3 shows a special 2D (6, 3) network, with six Zn(II) atoms at six corners and four bix and two double male ligands at six edges.4 is a (3, 4)-connected 3D network.5 and6 show the 2D (4, 4) network.7 consists of one-dimensional chains containing two alternative kinds of rings, [Zn2 (adc)2 ] and [Zn2 (bix)2 ]. The diverse structures indicate that the structures of the coordination polymers can be tuned by the right combination of appropriate flexible bis(imidazole) ligand, bix, the metal ions and dicarboxylate ligands.1 and2 are effective photocatalytic catalysts for the degradation of methyl orange. The luminescence of3 –7 and thermal stability of1 –7 were also investigated.